Type beta transforming growth factor in human platelets: release during platelet degranulation and action on vascular smooth muscle cells (The Rockefeller University Press, 1986)
A specific radioimmunoassay for type beta transforming growth factor (TGF-beta) was developed and used to show that human platelets treated with thrombin release TGF-beta as a consequence of degranulation. The thrombin concentrations required to induce release of TGF-beta parallel those concentrations that release the alpha-granule marker, beta- thromboglobulin. Related studies showed that TGF-beta acts on early passage, explant cultures of bovine aortic smooth muscle cells by inhibiting the effect of mitogens on proliferation of subconfluent cell monolayers yet synergizing with mitogens to stimulate growth of the same cells when cultured in soft agar. The results show that primary cultures of bovine aortic smooth muscle cells and established normal rat kidney cells behave similarly with regard to TGF-beta action. Moreover, the data suggest that platelet-mediated proliferation of aortic smooth muscle cells in vivo may not result solely from the stimulatory effect of platelet-derived growth factor (PDGF), but rather from an interaction of platelet factors which has the intrinsic ability to limit as well as stimulate mitosis.